Amplified spontaneous emission and optical gain characteristics of sexithiophene single crystals - Tahir, Muhammad; Sayyad, Muhammad Hassan; Said, Suhana Mohd; Sabri, Mohd Faizul Mohd; Sarker, Md Mahidur Rahman (Elsevier, 2020)
This paper reports optical properties of a single crystal thiophene/phenylene co-polymer 5,5ʺʺ'-diphenyl-2,2′:5′,2ʺ:5ʺ,2ʺ′:5ʺ′,2ʺʺ:5ʺʺ, 2ʺʺ'-sexithiophene (P6T). The P6T crystals demonstrate high charge carriers’ mobility and large photoluminescence quantum efficiency (PLQE). Herein, the stimulated emission of P6T is studied within wide range of pump energies –refers to energy per pulse – (from 19 ± 0.5 μJ/cm2 to 64.2 ± 0.5 μJ/cm2) through amplified spontaneous emission (ASE) measurements by using Nd-YAG femtoseconds tunable pulsed laser at 445 nm excitation wavelength (λexc). ASE measurements exhibit lower threshold energy density (Eth) i.e., ~26 ± 0.5 μJ/cm2 which confirms optical amplification in P6T at 632 nm emission wavelength. The ASE characteristics of P6T are also studied as a function of different λexc ranging from 425 to 475 nm to find the wavelength for optimum amplification. It is observed that the maximum optical amplification for P6T occurs at a λexc of 445 nm. These crystals exhibit large optical gains which are measured to be 69 cm−1, 53 cm−1 and 29 cm−1 at excitation energies of 91 ± 0.5 μJ/cm2, 66 ± 0.5 μJ/cm2 and 43 ± 0.5 μJ/cm2, respectively. PL measurements of P6T crystals demonstrate large value of the PLQE ~57.36%. This study suggests the potential of P6T single crystal as one of the good candidates among high optical gain materials of its kind for its possible applications in solid-state lasers, photodetectors and optical amplifiers. © 2020